Assessment of Environmental Risks in Construction Projects: A Case of Malaysia - Ansah, Richard Hannis; Sorooshian, Shahryar; Shariman, Mustafa; Duvvuru, Gomanth (IEOM Society, 2016)
Risk management is a concept which is increasingly becoming exceptional in a number of organizations. Several companies regularly set up a risk assessment procedure for performance improvement and profit maximization. In the construction industry, projects are enormously complex in nature and often involves significant budgets, and therefore reducing risks associated with project development should be key for every project manager. In this paper, risks associated with external sources have been identified and investigated in a case study. The analysis of the risks has been presented using risk priority number (RPN) to determine the failure modes in projects. From the results, the top risks included availability of labors, lack of technical know-how , use of old methodologies, inefficient dissemination of information, changes in government regulations, unrealistic contract time frame, licensing, permit, documents approvals, change of government department heads, bribery and corruption, difficulty in accessing credit facilities, obsolete technology and tools, market competition and conditions, inertia in government bureaucracies, changes in taxes, and import and export restrictions. This study aims to provide a decision tool for establishing failure modes and their priorities in Malaysian construction projects, thus, avoiding the major costly impact of the risky variables to projects in terms of budget, time and quality considering the scarce resources of construction companies.